TRANSFORMASI GEOMETRI MOTIF KAIN BATIK SURYA MAJAPAHIT DAN SISIK GRINGSING KABUPATEN MOJOKERTO - Ferima, Cynthia Alvionita (Zeta - Math Journal, 2020)
The batik cloth motif in Mojokerto Regency has several unique patterns, especially geometric patterns. Among the batik motifs in Mojokerto district that have geometric motifs are the majapahit sun and gringsing scales. For this reason, a study was conducted to formulate a problem, namely how the pattern of transformation in each type of batik cloth, namely Surya Majapahit and Sisik Gringsing batik, and the form of new motifs formed from a combination of previous motifs. This aims to determine the form of transformation of each motif and produce variations of new motifs. This research method includes field shape analysis, geometric transformation pattern analysis and simulation of making batik cloth motifs using the Geogebra Classic 5 application. The results obtained are to determine and combine the transformation patterns in the Surya Majapahit and Gringsing scales motifs resulting in a new variation of motifs, namely solar - gringsing. Based on the results of the analysis and discussion, it was concluded that the number of transformation patterns in the Surya Majapahit motif, namely 3 transformation patterns to form the main motive field and the combination of the transformation patterns possessed by Surya Majapahit and Sisik Gringsing's motifs produced new motifs.